Effects of foreign direct investment and trade on the prevalence of tobacco consumption in Africa: a panel study - Mustapha Immurana; Micheal Kofi Boachie; Kwame Godsway Kisseih (BMC, 2021)
Abstract Background As African governments take measures to enhance international trade and Foreign Direct Investment (FDI) inflows, a major concern is that, these measures can make Africa more vulnerable to the strategies of the tobacco industry. This concern is based on the fact that, each year, tobacco use is estimated to be responsible for the deaths of over eight million people in the world. However, there is very little empirical evidence to refute or confirm the above concern, especially in the African context. This study therefore investigates the effects of FDI and trade on the prevalence of tobacco consumption in Africa. Methods Data on a sample of 31 African countries for the period, 2010-2018 are used. The system Generalised Method of Moments (GMM) regression model is employed as the empirical estimation technique. Results The findings show that, FDI and trade have negative and positive significant association with the prevalence of tobacco consumption respectively. These findings are robust even after using different specifications and indicators of FDI and trade. Conclusion Rising trade (and not FDI) should be of concern to African governments in the quest to reduce the prevalence of tobacco consumption on the continent.